2013
DOI: 10.1017/jfm.2013.299
|View full text |Cite
|
Sign up to set email alerts
|

Transition delay in a boundary layer flow using active control

Abstract: Active linear control is applied to delay the onset of laminar-turbulent transition in the boundary layer over a flat plate. The analysis is carried out by numerical simulations of the nonlinear, transitional regime. A three-dimensional, localized initial condition triggering Tollmien-Schlichting waves of finite amplitude is used to numerically simulate the transition to turbulence. Linear quadratic Gaussian controllers based on reduced-order models of the linearized Navier-Stokes equations are designed, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 40 publications
0
42
0
Order By: Relevance
“…Another approach is the use of system identification methods in which low order models are obtained from a sample of input-output measurements. In particular the eigensystem realisation algorithm (ERA) (Juang & Pappa 1985) was recently used to construct reduced order models for fluid flows (Ma et al 2011;Illingworth et al 2012;Dadfar et al 2013;Semeraro et al 2013;Belson et al 2013;Flinois & Morgans 2016). ERA is based on the impulse response measurements and does not require prior knowledge of the high order system.…”
Section: Model Reduction and Localised Controlmentioning
confidence: 99%
See 3 more Smart Citations
“…Another approach is the use of system identification methods in which low order models are obtained from a sample of input-output measurements. In particular the eigensystem realisation algorithm (ERA) (Juang & Pappa 1985) was recently used to construct reduced order models for fluid flows (Ma et al 2011;Illingworth et al 2012;Dadfar et al 2013;Semeraro et al 2013;Belson et al 2013;Flinois & Morgans 2016). ERA is based on the impulse response measurements and does not require prior knowledge of the high order system.…”
Section: Model Reduction and Localised Controlmentioning
confidence: 99%
“…For localised transition control the disturbance is commonly represented by a localised body force placed upstream of the control actuators, see e.g. Bagheri et al (2009b); Semeraro et al (2011Semeraro et al ( , 2013; Belson et al (2013). For example, in Semeraro et al (2011) the disturbance was modelled as a localised initial condition that provides the maximum energy amplification of the perturbation at a given final time.…”
Section: Scope and Outline Of The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…In a low-turbulence environment the initial phase of the transition process is an exponential growth of Tollmien-Schlichting (TS) waves (Saric, Reed & Kerschen 2002). Both numerical and laboratory experiments have shown that it is possible to use linear control techniques to damp the amplitude of the instabilities by several orders of magnitude, with the consequences that the transition is delayed and the skin-friction drag is reduced (Lundell 2007;Bagheri & Henningson 2011;Goldin et al 2013;Semeraro et al 2013a). However, the linear control approach has not yet been established as a competitive technique in applied settings, and essentially all work is at a proof-of-concept level.…”
Section: Introductionmentioning
confidence: 99%